Glacial stages and post-glacial environmental evolution in the Upper Garonne valley, Central Pyrenees - Fernandes, M. (2020)
The maximum glacial extent in the Central Pyrenees during the Last Glaciation is known to have occurred before the global Last Glacial Maximum, but the succession of cold events afterwards and their impact on the landscape are still relatively unknown. This study focuses on the environmental evolution in the upper valley of the Garonne River since the Last Glaciation. Geomorphological mapping allows analysis of the spatial distribution of inherited and current processes and landforms in the study area. The distribution of glacial records (moraines, till, erratic boulders, glacial thresholds) suggests the existence of four glacial stages, from the maximum expansion to the end of the glaciation. GIS modeling allows quantification of the Equilibrium Line Altitude, extent, thickness and volume of ice in each glacial stage. During the first stage, the Garonne glacier reached 460m in the Loures-Barousse-Barbazan basin, where it formed a piedmont glacier 88km from the head and extended over 960km2. At a second stage of glacier stabilization during the deglaciation process, the valley glaciers were 12-23km from the head until elevations of 1000-1850m, covering an area of 157km2. Glaciers during stage three remained isolated in the upper parts of the valley, at heights of 2050-2200m and 2.6-4.5km from the head, with a glacial surface of 16km2. In stage four, cirque glaciers were formed between 2260m and 2590m, with a length of 0.4-2km and a glacial area of 5.7km2. Also, the wide range of periglacial, slope, nival and alluvial landforms existing in the formerly glaciated environments allows reconstruction of the post-glacial environmental dynamics in the upper Garonne basin. Today, the highest lands are organized following three elevation belts: subnival (1500-1900m), nival (1900-2300m) and periglacial/cryonival (2300-2800m).